Carcinoma of Maxillary Sinus. A case Presentation. - Blas Jorge González Manso; Orlando Jesús Sotolongo Terry; Ángel Luis Cruz Leiva (Medisur)
Tumors of the nasosinuous tract developed in the air cavities usually present a considerable growing before the patient feel any symptom or sign. Great part of the symptomatology is given due to the invasion of the tumor to neighbour structures such as oral and nasal cavities and orbits. A case of a 62 year-old male patient is presented after being under a dental extraction. A bucco-sinuous communication was diagnosed. It did not respond to different treatments and after some moths an epidermoid carcinoma of the right maxillary sinus appeared. It is of great interest to let this case been known in order to outstand the importance of an early diagnosis to get a better vital prognosis in this kinds of lesions.